Experiences of adult English language learners previously enrolled in English as a second language noncredit (ESLN) courses and currently enrolled in credit courses at a California community college - Zepeda, Mariana Macias (Kansas State University, 2022)
The purpose of the qualitative phenomenological study was to understand and describe the lived experiences of adult English language learners previously enrolled in English as a Second Language Noncredit (ESLN) courses who were persisting in credit coursework through the lens of Bean and Metzner’s (1985) nontraditional student attrition model. The study specifically focused on the experiences related to academic, psychological, environmental, and background factors as identified in Bean and Metzner’s model. In addition, the purpose of the study was to examine how student support services had an impact on their experiences in persisting in credit coursework. Via semi-structured interviews with eight participants, six themes were identified: Experiences as a credit student impacted by need to increase time dedicated to academics, strong attendance and major certainty helpful in academic success in classes, self-perceived English language abilities create stressful experiences in academic settings, faculty and family provide encouragement that create positive experiences, family responsibilities associated with age limit the time available to engage in academics and student support services provide resources that contribute to academic success.
Keywords: Adult English language learner; Persistence; Experiences